Body Mass Index, Blood Glucose, and Physical Activity as Determinants of Lactic Acid Levels among Textile Workers - Fauzi, Rachmawati Prihantina; Sumardiyono, Sumardiyono; Maria Paskanita Widjanarti; Suratna, Farhana Syahrotun Nisa; Chahyadhi, Bachtiar; Wijayanti, Reni; Ada, Yeremia Rante (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Textile industry is a labour-intensive industry with repetitive activities and heavy physical workload, thereby likely to cause metabolic fatigue as reflected by high levels of lactic acid. This study aims to examine the independent and combined associations of Body Mass Index (BMI), blood glucose levels, and physical activity with elevated lactic acid levels among textile workers. A cross-sectional analytical study was conducted among 80 textile workers selected using at a textile company in Surakarta between January and March 2023. A series of binary logistic regression analysis were conducted, adjusting for age and sex, with statistical significance set to p < 0.05. The overall statistical significance of the model was found to be significant (p < 0.001) and the explanatory power of the model was very high (Nagelkerke R² = 55.2%). The most dominant factor associated with high levels of lactic acid was found to be the level of blood glucose above 180 mg/dL (aOR = 15.525; 95% CI: 3.003–80.263), followed by BMI over 25 kg/m² (aOR = 9.695; 95% CI: 2.155–43.617). Physical activity was found to be protective (aOR = 0.182; 95% CI: 0.037–0.891), but age and sex were not significant. These results suggest that metabolic behavioural factors are significantly associated with elevated lactic acid levels, which may indicate metabolic fatigue among textile employees. These findings highlight the importance of strengthening metabolic screening and promoting physical activity within occupational health programmes.